The Structure and Role of Intramuscular Connective Tissue in Muscle Function - Purslow, Peter P. (Frontiers in Physiology, 2020)
Each individual muscle is surrounded by epimysial connective tissue and within the muscle there are two distinct extracellular matrix (ECM) structures, the perimysium and endomysium. Together, these three ECM structures make up the intramuscular connective tissue (IMCT). There are large variations in the amount and composition of IMCT between functionally different muscles. Although IMCT acts as a scaffold for muscle fiber development and growth and acts as a carrier for blood vessels and nerves to the muscle cells, the variability in IMCT between different muscles points to a role in the variations in active and passive mechanical properties of muscles. Some traditional measures of the contribution of endomysial IMCT to passive muscle elasticity relied upon tensile measurements on single fiber preparations. These types of measurements may now be thought to be missing the important point that endomysial IMCT networks within a muscle fascicle coordinate forces and displacements between adjacent muscle cells by shear and that active contractile forces can be transmitted by this route (myofascial force transmission). The amount and geometry of the perimysial ECM network separating muscle fascicles varies more between different muscle than does the amount of endomysium. While there is some evidence for myofascial force transmission between fascicles via the perimysium, the variations in this ECM network appears to be linked to the amount of shear displacements between fascicles that must necessarily occur when the whole muscle contracts and changes shape. Fast growth of muscle by fiber hypertrophy is not always associated with a high turnover of ECM components, but slower rates of growth and muscle wasting may be associated with IMCT remodelling. A hypothesis arising from this observation is that the level of cell signalling via shear between integrin and dystroglycan linkages on the surface of the muscle cells and the overlying endomysium may be the controlling factor for IMCT turnover, although this idea is yet to be tested.